Sumbangsih Pikiran Filsafat David Hume (1711-1776) terhadap Teologi dan Relevansinya Bagi Umat Beragama - Manuk, Andreas Geleda; Liwu, Dominggus Bara; Kudre, Gabriel (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This paper discusses the contribution of the philosophical thought of David Hume (1711-1776) to theology and its relevance to religious people. Hume, as an empiricist, emphasized that morality comes from human feelings and experiences, not from reason or divine revelation. He proposed that good and bad are determined by compassion for others, which is in line with the teaching of charity in Catholic theology. Through a literature analysis approach, this article explores three main Hume thoughts: morality as a product of feeling, the evaluation of actions based on consequences, and the importance of virtue. Hume also criticized the traditional view that separates reason from morality, asserting that it is feelings that are the basis of moral judgment. The relevance of Hume's thought to religious people lies in its ability to encourage interfaith dialogue, find common ground in moral values, and promote empathy in the practice of daily life. The conclusion of this paper is that Hume's moral thought offers an important framework for building a more just, harmonious, and loving society in today's multicultural era.